The Effect of Ethanolic Extract of Pandanus tectorius Leaves on Spatial Memory Ability and GCMS Analysis of Potentially Therapeutic Compounds - Yohana Krisostoma Anduk Mbulang; Magi Melia Tanggu Rame; Cahyani Purnasari; Aloisius Masan Kopong (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Free radicals are known to damage the hippocampus and will decrease spatial memory. This condition will decrease cognitive function. This study focused on discovering the ability of the ethanolic extract of Pandanus tectorius leaves (EEPTL) to increase spatial memory and its active compounds using GC-MS. This study used twenty-five male mice (Mus musculus) divided into five groups. Three groups were given EEPTL orally using 100, 200, and 300mg/kg BW doses; one negative control (ethanol 10%) and one positive control (donepezil 0.65mg/kg BW). Each group was induced using ethanol 10% for three weeks (0.5mL/day) and tested for spatial memory using the Y-maze method. The result showed that EEPTL significantly increases mice's spatial memory ability (P<0.005). The most effective EEPTL dose is 300 mg/kg BW. GC-MS results showed that some active compounds in EEPTL are palmitic acid, stearic acid, coumarin, and 3-benzoyl-4-phenyl-ethyl linoleic. These results indicate that EEPTL increases spatial memory and contain several fatty acids, volatile oil, and phenols.